2016
DOI: 10.1111/jpn.12647
|View full text |Cite
|
Sign up to set email alerts
|

Zinc methionine and laminarin have growth‐enhancing properties in newly weaned pigs influencing both intestinal health and diarrhoea occurrence

Abstract: Three experiments were conducted to investigate the interaction between zinc methionine (ZnM) and laminarin (LAM) on piglet growth performance and intestinal health post-weaning. Experiment 1 was designed as 2 × 2 factorial with four treatments [n = 8, weaning age (WA) 24 days, live weight (LW) 7.15 kg]: (i) basal diet (BD); (ii) BD + 500 mg/kg ZnM; (iii) BD + 300 mg/kg LAM; and (iv) BD + 500 mg/kg ZnM + 300 mg/kg LAM. There was an interaction (p < 0.05) between LAM and ZnM. Pigs that were offered the LAM diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…Moreover, the use of high zinc levels in pig feeds has led to heavy metal contamination in the soil, raising environmental concerns [115]. Recently, Bouwhuis et al [117] reported that organic zinc [zinc methionine (ZnM)] could be used as a substitute for the inorganic zinc (ZnO) in the pig diet. In fact, organic zinc can be supplemented in lower doses (up to 500 mg/kg feed) compared to ZnO [117].…”
Section: Feed Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the use of high zinc levels in pig feeds has led to heavy metal contamination in the soil, raising environmental concerns [115]. Recently, Bouwhuis et al [117] reported that organic zinc [zinc methionine (ZnM)] could be used as a substitute for the inorganic zinc (ZnO) in the pig diet. In fact, organic zinc can be supplemented in lower doses (up to 500 mg/kg feed) compared to ZnO [117].…”
Section: Feed Additivesmentioning
confidence: 99%
“…Recently, Bouwhuis et al [117] reported that organic zinc [zinc methionine (ZnM)] could be used as a substitute for the inorganic zinc (ZnO) in the pig diet. In fact, organic zinc can be supplemented in lower doses (up to 500 mg/kg feed) compared to ZnO [117]. In this study, the inclusion of ZnM resulted in improved faecal scores and the intestinal architecture compared to that observed in pigs supplemented with ZnO.…”
Section: Feed Additivesmentioning
confidence: 99%
“…In swine, 24 studies have been published in the last 10 years on the effects of supplementation with brown seaweeds, or their extracts, on gut health: Ascophyllum nodosum [42,60,72], Ecklonia cava [63], Laminaria digitata [64,80,81], Laminaria hyperborea [82,83], Laminaria digitata and Laminaria hyperborea association [84], Laminaria spp. [58,59,65,67,[69][70][71][85][86][87][88][89][90]. Brown seaweeds titrated in alginic acid polysaccharides have also been studied [63].…”
Section: Prebiotic Functionmentioning
confidence: 99%
“…Previous studies have focused on methionine Zn chelates. These studies indicated that methionine Zn chelate has a positive effect on growth performance, meat quality and intestinal health of pigs [14,15]. The ASP is the common precursor for the synthesis of methionine, while, the effects of Zn with aspartate on pigs are rarely reported.…”
Section: Discussionmentioning
confidence: 99%